Biodiplomacy: Efforts to Achieve Fairness in Cross-Border Genome Data Transfers - Tri Andika (The Indonesian Journal of International Clinical Legal Education, 2025)
Genome data is currently becoming important data in precision medicine era. The importance of genome data has resulted in increased collection activities worldwide. Until now, there have been no international regulations regarding the activity of sending human genome data across national borders. This has an impact on unequal utilization between countries. Fairness in the use of genome data between countries and the role of Indonesian diplomacy in realizing fairness in the use of genome data are issues in this research. The research method used in this study is a normative legal method that focuses to find and analyze regulations on the regulation of genome data protection in genome data transfer between countries with statute and conceptual approach. The Result shows that in the face of the international regulatory vacuum, countries are divided into three groups, namely countries that prohibit the transfer of genome data, countries that allow it with government permission, and countries that allow the transfer of genome data. To fill the gap in international regulations, Indonesia's diplomatic role is needed to ensure the security of human genome data sent outside its territory.